The Treatment of the Corn-Knob as A Raw Material for Making Furfural - Nurul Hidajati (Jurnal ILMU DASAR, 2007)
This research is conducted to determine the furfural rendement of the corn-knob with the varieties of heating periods of 2; 2.5; 3; 3.5; and 4 hours. This methods used were, first, the hydrolysis of the corn-knob using HCl with the varieties of heating periods as mentioned above. Then it was continued by the extraction and purification of the furfural through distillation. The resulted furfural is identified by the acetic-anilin color reaction, infrared spectrophotometer, refractive index and GC-MS. The identification result was compare with the furfural standard. The result of this research shows that average rendement was 8.43% for the heating period of 2 hours, 9.67%, for 2.5 hours, 11.57% for 3 hours, 13.30% for 3.5 hours and 12.59% for 4 hours.